A cucurbit[6]uril-based supramolecular assembly test strip for immediate detection of nitrofuran antibiotics in water. Issue 44 (21st October 2020) - Shi, Lulu; Liu, Mei; Fang, Cao; Zhu, Xiaofei; Li, Hui
Abstract : A CB[6]-based supramolecular assembly has been designed and prepared into test strips, which can detect nitrofuran antibiotics by the naked eye. Abstract : A cucurbit[6]uril-based (CB[6]) luminescent supramolecular assembly [CdL4 ] 2− ·CB[6] (1 ) has been successfully synthesized using anthracene carboxylic acid (HL) as a structure-directing agent. It has high water stability, easy regeneration ability and rapid response time. Investigation reveals that among the 12 species of antibiotics under investigation, 1 displayed high selectivity toward nitrofurazone (NFZ) and nitrofurantoin (NFT) through luminescence quenching, and the detection is not disturbed by the presence of other species. The limit of detection (LOD) for NFZ and NFT were calculated to be 90 and 49 ppb, respectively, indicating the ultra-sensitivity. Further studies reveal that 1 can be successfully applied for the detection of NFZ in simulated wastewater and urine with satisfactory results. More exhilaratingly, test strips based on 1 were successfully prepared, which can be used for naked-eye sensing of NFZ and NFT in water with emission color changes from bright blue to dark. These interesting results indicate that 1 can serve as a promising luminescent sensor in various potential applications.